Combination therapy versus monotherapy: retrospective analysis of antibiotic treatment of enterococcal endocarditis - Razan Saman; Christopher P. Primus; Robert West; Simon J. Woldman; Jonathan A. T. Sandoe (BMC Infectious Diseases)
Abstract Background Guidelines suggest treating fully penicillin-susceptible Enterococcus faecalis strains causing infective endocarditis with amoxicillin combined with gentamicin or ceftriaxone, but clinical evidence to support this practice is limited and monotherapy cohorts were excluded from studies. We describe antibiotic treatment, complications, and outcomes in patients with Enterococcus faecalis infective endocarditis, specifically comparing monotherapy versus combination therapy. Methods Retrospective analysis of prospectively collected cohort of patients with definite or possible infective endocarditis from 2 English centres between 2006 and 2021. The primary outcome was 30-day mortality. Secondary outcomes included acute kidney injury, relapse, and clinical cure. Results 178 individuals were included: median age was 72 years (interquartile range 60–79), male sex majority (138, 78%) and mostly native valve endocarditis (108, 61%). Thirty-nine patients (22%) received monotherapy (penicillin/glycopeptide/linezolid/daptomycin), 128 (72%) combination with gentamicin, 11 (6%) combination with ceftriaxone. Patients on combination therapy with gentamicin had a statistically significant lower 30-day mortality than those treated with monotherapy (21 (16.4%) versus 15 (38.5%) p = 0.035) and higher rates of clinical cure (101 (78.9%) versus 23 (59.0%) p = 0.018). Patient receiving gentamicin were more likely to experience acute kidney injury (64 (50%) versus 11 (28.2%) p = 0.057). Ceftriaxone combination was associated with poor outcomes, but the sample size was small. Conclusion Patients treated with combination gentamicin therapy had better clinical outcomes than patients treated with monotherapy. Low-dose gentamicin regimens were associated with acute kidney injury. Patients treated with combinations were different to those treated with monotherapy and confounding remains a concern with observational analyses. An adequately powered clinical trial is needed to determine optimal treatment of enterococcal endocarditis. Clinical trial number Not applicable.